Measurements of Higgs boson production cross-sections in the H → τ+τ− decay channel in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rodriguez Bosca, Sergi; et al. (Journal of high energy physics, 2022)
Measurements of the production cross-sections of the Standard Model (SM) Higgs boson (H) decaying into a pair of τ-leptons are presented. The measurements use data collected with the ATLAS detector from pp collisions produced at the Large Hadron Collider at a centre-of-mass energy of = 13 TeV, corresponding to an integrated luminosity of 139 fb−1. Leptonic (τ → ℓνℓντ) and hadronic (τ → hadrons ντ) decays of the τ-lepton are considered. All measurements account for the branching ratio of H → ττ and are performed with a requirement |yH| < 2.5, where yH is the true Higgs boson rapidity. ...
Gesehen am 02.12.2022
The ATLAS collaboration: G. Aad, B. Abbott, D.C. Abbott, A. Abed Abud, K. Abeling, D.K. Abhayasinghe, S.H. Abidi, A. Aboulhorma, H. Abramowicz, H. Abreu, Y. Abulaiti, A.C. Abusleme Hoffman, B.S. Acharya, B. Achkar, L. Adam, C. Adam Bourdarios [und viele weitere]
Im Titel sind die Zeichen "+" und "-" sind hochgestellt